Nuclear shape phase transition within a conjunction of γ-rigid and γ-stable collective behaviors in deformation-dependent mass formalism. (14th November 2016) - Chabab, M; Batoul, A El; Lahbas, A; Oulne, M
Abstract: In this paper, we present a theoretical study of a conjunction of γ -rigid and γ -stable collective motions in critical point symmetries of the phase transitions from spherical to deformed shapes of nuclei using an exactly separable version of the Bohr Hamiltonian with a deformation-dependent mass term. The deformation-dependent mass is applied simultaneously to γ -rigid and γ -stable parts of this famous collective Hamiltonian. Moreover, the β part of the problem is described by means of Davidson potential, while the γ -angular part corresponding to axially symmetric shapes is treated by a harmonic oscillator potential. The energy eigenvalues and normalized eigenfunctions of the problem are obtained in compact forms by making use of the asymptotic iteration method. The combined effect of the deformation-dependent mass and rigidity as well as harmonic oscillator stiffness parameters on the energy spectrum and wave functions is duly investigated. Also, the electric quadrupole transition ratios and energy spectrum of some γ -stable and prolate nuclei are calculated and compared with the experimental data as well as with other theoretical models.